Respuesta :

9514 1404 393

Answer:

  3] 4x -3y = 3

  4] x -2y = -2

  5] y = 3; x = -1

Step-by-step explanation:

3] The standard form equation can start with the form ...

  (y2 -y1)(x -x1) -(x2 -x1)(y -y1) = 0

  (-9 -(-1))(x -0) -(-6 -0)(y -(-1)) = 0

  -8x +6(y +1) = 0

In standard form, we want the leading coefficient to be positive, and we want the constant to be on the right side of the equal sign. We also want the coefficients to be mutually prime (all common factors removed). So, dividing the equation by -2 gives ...

  4x -3(y +1) = 0

  4x -3y -3 = 0

  4x -3y = 3 . . . . standard form equation

__

4] Same deal, different points.

  (6 -(-5))(x -(-12)) -(10 -(-12))(y -(-5)) = 0

  11(x +12) -22(y +5) = 0

  x -2y = -2 . . . . simplify to standard form

__

5] A horizontal line has the equation y = constant. A vertical line has the equation x = constant. To make these lines go through the given point, the constants need to be equal to the corresponding coordinates:

  y = 3

  x = -1

Ver imagen sqdancefan